The interaction between primate blood and mouse islets induces accelerated clotting with islet destruction. - Badet, L; Titus, T; Metzen, E; Handa, A; McShane, P; Chang, L; Giangrande, P; Gray, D (2002)
BACKGROUND: Mouse islets transplanted under the renal subcapsular space of cynomolgus monkeys are subject to a form of hyperacute rejection, the mechanism of which is unclear. As islets are in contact with whole blood at the time of transplantation, the effect of platelets and the coagulation cascade on islet destruction was assessed. METHODS: Coagulation was assessed using thromboelastography on citrated/recalcified human blood samples with freshly isolated C57/Bl6 mouse islets. A dynamic islet perifusion system was used to assess the effect of islets on blood cells and coagulation factors. Cytotoxicity was evaluated using (51)Cr labelled islets incubated with human blood and islet destruction was also evaluated using a histological grading system. Continuous PO(2) measurements were made in a static incubation system to assess the role of hypoxia in islet destruction. RESULTS: Mouse islets incubated in human blood induced accelerated coagulation and rapid consumption of platelets within 15 min. Within 1 h of incubation, 52% of mouse islets exposed to xenogeneic human blood showed features of severe damage with necrosis when compared with islets incubated in syngeneic blood. Specific lysis of the xenogeneic islets was demonstrable (Mean percentage lysis: 48%, P < 0.05 vs. control) after 4 h incubation in human blood. Oxygen levels remained constant at a level adequate to maintain islet viability in separate experiments. CONCLUSION: Mouse islets induce rapid activation of the clotting cascade and platelet consumption in vitro when exposed to human blood, which correlated with histological evidence of significant destruction demonstrable within 1 h of exposure to human or non-human primate blood. This in vitro model has features which appear to correlate with the islet destruction seen in vivo and could be a useful model for the study of the mechanisms underlying the rapid destruction of xenogeneic islets in primate recipients.